Functional Improvements by Controlled Suture Tension in Arthroscopic Rotator Cuff Repair - Shinji Imai, MD, PhD (JBJS Open Access)
Background:. Although a certain degree of tension in bridging sutures is required for proper tendon healing following suture-bridge rotator cuff repair, excessive suture tension may be detrimental to tendon healing. This study aimed to investigate the effects of bridging suture tension on clinical outcomes and tendon healing. We hypothesized that fixed, low tension of the bridging sutures would improve the tendon healing rate and clinical outcomes compared with maximum manual tensioning. Methods:. A group of 39 patients with a rotator cuff tear were treated with arthroscopic suture-bridge rotator cuff repair, in which the bridging sutures were uniformly tensioned to 20 N (group A). A separate group of 37 patients was treated with the same suture construct, but the sutures were tensioned by maximum manual pulling (mean tension, 36.1 N; group B). The visual analog scale (VAS) score for pain, active anterior elevation, external and internal rotation, and Constant score were compared between the groups preoperatively and at 1, 3, and 6 months and 1 and 2 years postoperatively. Anatomical healing was evaluated using magnetic resonance imaging (MRI) at 1 year after surgery. Results:. At 6 months postoperatively, all clinical values had improved in both groups. The Constant score (p < 0.001), VAS pain score (p < 0.001), and anterior elevation (p = 0.004) were significantly better in group A than in group B. Two years postoperatively, there was no significant difference between groups A and B in the Constant score (p = 0.847), VAS pain score (p = 0.991), and anterior elevation (p = 0.855). Group A demonstrated a significantly lower retear rate (3 of 39, 7.7%) than group B (9 of 37, 24.3%) (p = 0.0467). Conclusions:. Double-row suture-bridge repairs with fixed, low tension led to superior clinical outcomes at 6 months and a superior tendon healing rate at 1 year compared with repairs with higher suture tension. However, the clinical outcomes did not differ significantly at 2 years between the 2 tensioning methods. Level of Evidence:. Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.